Development of the Vestibular Lamina in Human Embryos: Morphogenesis and Vestibule Formation - Qiu, Tengyang; Teshima, Tathyane H. N.; Hovorakova, Maria; Tucker, Abigail S. (Frontiers in Physiology, 2020)
The vestibular lamina (VL) is a transient developmental structure that forms the lip furrow, creating a gap between the lips/cheeks and teeth (oral vestibule). Surprisingly little is known about the development of the VL and its relationship to the adjacent dental lamina (DL), which forms the teeth. In some congenital disorders, such as Ellis-van Creveld syndrome, development of the VL is disrupted and multiple supernumerary frenulum form, physically linking the lips and teeth. Here we assess the normal development of the VL in human embryos from 6.5 weeks (CS19) to 13 weeks of development, showing the close relationship between the VL and DL, from initiation to differentiation. In the anterior lower region, the two structures arise from the same epithelial thickening. The VL then undergoes complex morphogenetic changes during development, forming a branched structure that separates to create the vestibule. Changing expression of Keratins highlight the differentiation patterns in the VL, with fissure formation linked to the onset of Filaggrin. Apoptosis is involved in removal of the central portion of the VL to create a broad furrow between the future cheek and gum. This research forms an essential base to further explore developmental defects in this part of the oral cavity.